Coping with Open Innovation: Responding to the Challenges of External Engagement in R&D - Salter,A; Criscuolo,P; Ter,Wal ALJ (California Management Review, 2014)
Open innovation often requires wholesale changes to the nature of R&D. However, academic research and managerial practice have paid little attention to the challenges that individuals face in the daily pursuit of open innovation. As a result, there is little understanding of how individuals cope with open innovation, and which organizational practices can support them in this role. Drawing on the experiences of R&D professionals, this article identifies four specific challenges and coping strategies of individuals engaged in open innovation. It proposes a range of open innovation practices that organizations can implement to better equip their staff to undertake effective external engagement.